Social Network Analysis as an Organizational Diagnostic Tool: The Case of Small Business in Russia - Rasskazov, Sergey; Rubtcova, Mariia; Derugin, Pavel; Pruel, Nikolay; Malychev, Valeriy (International Review of Management and Marketing, 2016)
The science of social networks is at the intersection of computer science, communication studies, mathematics and sociology. The first area is already ‘invested’ by communications networks, hardware and software, and has attracted many users. Communication science studies the network not only as a computer network, but also as a network of discourse. Contributions of mathematics; the Theory of Graphs and various related calculations. ‘Weak’ in this triad is a sociological interpretation of quantitative ratios network. The purpose of this work is defining the concept of ‘social network analysis as an organisational diagnostic ‘tool’, and its implementation using a quantitative analysis method. The article considers the following questions: the definition of the diagnostic process in relation to social networking organisation; the possibility of social networking quantitative analysis; the illustration of how to use the theory of social capital as a sociological basis for the social networks diagnostics in the small business and the calculations of illustrative indicators and real networks in the case of a small business organization in Russia. Data processing was carried out with the use of UciNet. As a result, the classes (diagnosis) of organisational social networks are offered, and opportunities, along with their limits of the application of quantitative indicators making up the method of social network analysis to diagnose the network of organisations with a variety of responses, are presented. Keywords: social network analysis, organizational diagnostic tools, measurement of social capital, management sociology. JEL Classifications: D85, M12, M14